CHRONIC MYELOGENEOUS LEUKEMIA TRANSFORMATION INTO ACUTE LYMPHOBLASTIC LEUKEMIA - Endah Indriastuti; Arifoel Hajat (INDONESIAN JOURNAL OF CLINICAL PATHOLOGY AND MEDICAL LABORATORY, 2019)
Introduction : Chronic myelogeneous leukemia (CML) is a myeloproliferative neoplasm that can progress into various conditions. Transformation of CML into acute lymphoblastic leukemia (ALL) is a rare case. Case :  A 22-year-old male with history of CML since 2014 and positive BCR-ABL p210 in 2017 came with complaint of weakness. Physical examination showed hepatosplenomegaly. CBC results Hb  7.1 g/dL, WBC 290,620/μL, platelet 434,000/μL. Blood smear evaluation (BSE) suggested CML blastic crisis dd AML-M5. Patient’s condition got worse. CBC result showed  WBC 96,770/μL and  platelet 7,000/μL in 2 weeks later. BSE was dominated by mononuclear cells with scanty blue cytoplasm, no granules, no auer rods, loose chromatine and indistinct nucleoli, suggesting lymphoblasts with a proportion of 60%. Bone marrow aspiration (BMA) and immunophenotyping was done to confirm BSE. The BMA result was dominated by lymphoblast, consistent with ALL. The immunophenotyping result was CD10+, CD34+(0,99%), CD79a+, HLA-DR+, and CD20+.  Molecular examination showed positive RUNX1 and NRAS while negative FLT3, NPM1 and del(5q). Discussion : BCR-ABL gene can be found both in CML and ALL. CML transformation into ALL had been reported to be related with deletion of a transcription gene. Diagnosis of ALL can be established by BMA and immunophenotyping. CD34+ expression of lymphoblast in ALL can be varied, but in this case was minimal. Conclusion : Patient with history of CML showed an ALL picture based on BSE, BMA and immunophenotyping suggesting CML transformation into ALL although CD34+ expression was minimal.